Optimization and efficacy studies of Laccase immobilized on Zein-Polyvinyl pyrrolidone nano fibrous membrane in decolorization of Acid Red 1 - G. Ranimol (IWA Publishing, 2021)
Azo dyes are widely used in textile industries. A significant portion of these recalcitrant dyes are being discharged to the natural waters. Due to their low biodegradability they pose serious pollution problems if untreated. In this work, decolourization studies of Acid Red 1 (AR1) by laccase enzyme immobilized onto zein–polyvinyl pyrrolidone (PVP) composite nanofiber is done. The nanofibers were characterized by scanning electron microscopy (SEM) and Fourier-transform infrared (FTIR) analysis. pH and temperature profiles of immobilized enzyme were found to be broader than its free counterpart. The Km value was found to be 0.243 mM for free laccase and 0.958 mM for immobilized laccase. Similarly, Vmax for the free enzyme was 3.572 U/mg compared to 2.48 U/mg of immobilized laccase. The relative activity of immobilized laccase was 64.91% after storage for 30 days at room temperature while it was 28.64% for free laccase. The temperature and pH for AR 1 decolorization were optimized and was found to be 60 °C and 5, respectively. Also, decolorization percentage was found to be 91.67% for immobilized laccase and 72.03% of free laccase in the presence of natural mediators like vanillin. From phytotoxicity studies it was found that the germination rate, shoot and root length was increased compared to untreated dye. Therefore, zein–PVP nanofiber immobilized laccase could be an ideal candidate for the textile dye decolorization. HIGHLIGHTS Textile effluents cause serious pollution problem in the environment.; Effectiveness of laccase enzyme in the decolorization of Acid Red-1 is studied.; Laccase was used either in the free form as well as immobilized in the zein–polyvinyl pyrrolidone nanofiber membrane.; The immobilized enzyme showed greater capacity for decolorization.;